Analysis of risk factors and postoperative complications in patients with crohn’s disease - Saad Hossne, Rogério [UNESP]; Sassaki, Ligia Yukie [UNESP]; Baima, Julio Pinheiro [UNESP]; de Meira JÚnior, José Donizeti [UNESP]; Campos, Luana Moraes [UNESP] (FapUNIFESP (SciELO), 2018)
Background – The post-operative complications rate is greater in patients with Crohn’s disease than in other abdominal surgeries due to other benign conditions. Prevention and management of such complications are important factors in the care of these patients. Objective – The objectives of this research are to analyze the rate of postoperative complications and the major risk factors in patients with Crohn’s disease. Methods – A descriptive and retrospective study based on analysis of medical records of patients with Crohn’s disease undergoing ileal and/or colonic resection, which analyzed the main surgical complications and their major risk factors. Results – Forty-four surgical procedures and thirty-seven patients were analyzed. Most were female (56.7%). Postoperative complications were observed in 18 (40.9%) surgeries. The disease duration (P=0.04), the penetrating behavior (P=0.013), the time between diagnosis and the first surgery (P=0.04), malnutrition with low body mass index (BMI), duration of surgery (P=0.016), and the size of the removed specimen (P=0.014) were associated with higher rates of complications. The use of drugs blocking tumor necrosis factor up to eight weeks before surgery was not significantly associated with higher complications rates or increased need for reoperation. Conclusion – The complication rate observed in this study is similar to published data. The duration of the disease, the penetrating behavior, the size of the removed specimen, the duration of the surgery, and BMI are important risk factors for perioperative complications in Crohn’s disease.
Análise dos fatores de risco e complicações pós-operatórias em pacientes portadores de doença de crohn
Keywords: Digestive system surgical procedures; Inflammatory bowel disease; Postoperative complications; Risk factors; Secondary prevention